Nature exposed : photography as eyewitness in Victorian science - Tucker, Jennifer, 1965- (Johns Hopkins University Press, 2005)
"In Nature Exposed, Jennifer Tucker studies the intersecting trajectories of photography and modern science in late Victorian Britain. She examines the role of photograph as witness in scientific investigation and explores the interplay between photographic practice and scientific authority." "Recovering the controversies and commentary surrounding early scientific photography and drawing on a wide range of new sources and critical theories, Tucker deepens our understanding of Victorian science, its rich visual culture, and alternative forms of knowledge, including psychial research and theorizing about canals on Mars."--Jacket